2018
DOI: 10.1063/1.5033492
|View full text |Cite
|
Sign up to set email alerts
|

The effect of alternative propellants on the electron drift instability in Hall-effect thrusters: Insight from 2D particle-in-cell simulations

Abstract: Hall-effect thrusters (HETs) operated with xenon are one of the most commonly used electric propulsion technologies for a wide range of space missions, including drag compensation in low Earth orbit, stationkeeping, and orbital insertion, as access to space becomes more affordable. Although anomalous electron transport, the electron drift instability (EDI), and secondary electron emission (SEE) have been studied experimentally and numerically in xenon-based HETs, the impact of alternative propellants is still … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 54 publications
(83 reference statements)
0
10
0
Order By: Relevance
“…The code is parallelized via MPI through a domain decomposition. It has been verified with the 1D helium benchmark of Turner et al [19] (further details in [28,29]) and extensively used to simulate the radial-azimuthal plane of a Hall Thruster [28,30,31]. For this benchmark, the code was adapted to the axial-azimuthal plane and accelerated via a load-balancing algorithm (adjusting periodically the size of each processor domain to have approximately the same number of particles inside each processor).…”
Section: Group Lpp: T Charoy a Tavant A Bourdon P Chabertmentioning
confidence: 99%
“…The code is parallelized via MPI through a domain decomposition. It has been verified with the 1D helium benchmark of Turner et al [19] (further details in [28,29]) and extensively used to simulate the radial-azimuthal plane of a Hall Thruster [28,30,31]. For this benchmark, the code was adapted to the axial-azimuthal plane and accelerated via a load-balancing algorithm (adjusting periodically the size of each processor domain to have approximately the same number of particles inside each processor).…”
Section: Group Lpp: T Charoy a Tavant A Bourdon P Chabertmentioning
confidence: 99%
“…Various values of the effective z k were reported in different simulations [195], [193], [194], [24]. Effects of Secondary Electron Emission (SEE) and different propellants were studied [194], [24] and it was shown that the EDI activity is affected by the reduced electron temperature due to sheath cooling. Besides, SEE induces large electron transport due to near-wall effects.…”
Section: Current and Future Challengesmentioning
confidence: 99%
“…The important role of the modified two-stream instability, due to a finite z k , leading to strongly anisotropic heating and large scale radial structures in the anomalous current, was emphasized [195]. Various values of the effective z k were reported in different simulations [195], [193], [194], [24]. Effects of Secondary Electron Emission (SEE) and different propellants were studied [194], [24] and it was shown that the EDI activity is affected by the reduced electron temperature due to sheath cooling.…”
Section: Current and Future Challengesmentioning
confidence: 99%
“…, where n e and Ẽ are the electron density and the self-consistent electric field and are calculated as for unmagnetized ion-sound turbulence. These results were validated against some particle-in-cell (PIC) simulations [18][19][20] .…”
mentioning
confidence: 88%